Word Classes in Children's Definitions - Jelaska, Zrinka; Novak Milić, Jasna (2009)
The organization of the mental lexicon may be investigated, among other ways, through the use of word definitions. Most research on word definition development analyzes children's definitions of nouns, followed by verb definitions. Other types of words were given far less or hardly any attention. Data on adjective definitions did not show as clear a picture as noun definitions. The problem was inconsistent development in the definition form (not in the semantic content): there was a tendency to use noun and verb forms together with adjectival forms (synonym-type definitions). The data analyzed in this paper was part of a larger scale study involving participants (age 3-20) interviewed on the meanings of various words (some grammatical words were included, i.e. pronouns and prepositions). The mental lexicons of child participants are discussed based on their definitions, content and form. The main goal was to get an insight into the relationship between word classes, e.g. parts of speech. A tendency to prefer lexical members from homophonic pairs or more typical lexical words (nouns <- adjectives <- prepositions) than less typical was observed. It happened both in the word defined, as well as the form of the definition (which is in line with previous research).
Projekt MZOS
Projekt MZOS
ENG